Future Prospect of Oral Microbiota Influencing Allergy/Asthma Development - Cai, Yue; Zhao, Yanqin; Kang, Yongbo; Yang, Ying (Frontiers in Microbiology, 2022)
Allergic diseases have become a primary public health issues in a moderately prosperous society. Colonization of microorganism early in life appears to be significance of guiding the regulation of childhood immune system maturation and allergic development. Since the nonnasality is the first position where most foreign antigens meet the immune system, the oral microbiota may play a key role in the development of allergies. However, study on the effects of oral microorganism on allergy/asthma is very restricted and should be actively investigated. It requires considerable effort to enrich our knowledge in this area of relationship between the oral cavity and allergy/asthma. In order to promote the rapid progress of relevant research. In this review, we aimed to provide several insights into the role of the oral microbiota in allergy/asthma while prospecting the future directions.